Development and research of a model for differential diagnosis of latent late syphilis and false-positive serological reactions on immunochips with a panel of 12 Treponema pallidum antigens - Marina V. Shpilevaya; Georgiy L. Katunin; Alexey A. Kubanov (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
The aim - to find the optimal attributing rules to distinguish groups of latent stages of syphilis and false positive serological tests of using multivariate discriminant analysis Material and methods. The objects of the study were serum samples from patients with late latent (N=34) syphilis and false positive serological tests (N=31). The samples were studied to determine IgG and IgM levels using indirect immunofluorescent reaction with immunochip containing recombinant antigens T. pallidum Results The mathematical model allows to differentiate with a high degree of confidence patients with late latent syphilis and with false-positive serological reactions to syphilis. Conclusions. . Multivariate discriminant analysis makes possible to create reliable mathematical models to classify patients with late latent syphilis and with false-positive serological reactions to syphilis.